2020
DOI: 10.48550/arxiv.2012.09124
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pre-Shape Calculus: Foundations and Application to Mesh Quality Optimization

Daniel Luft,
Volker Schulz

Abstract: Deformations of the computational mesh arising from optimization routines usually lead to decrease of mesh quality or even destruction of the mesh. We propose a theoretical framework using pre-shapes to generalize classical shape optimization and -calculus. We define pre-shape derivatives and derive according structure and calculus theorems. In particular, tangential directions are featured in pre-shape derivatives, in contrast to classical shape derivatives featuring only normal directions. Techniques from cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…In this work, we want to approach these two aspects differently. By using preshape calculus techniques introduced in [12], we propose regularization techniques for shape gradients with two goals in mind. First, the required computational burden should be limited.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this work, we want to approach these two aspects differently. By using preshape calculus techniques introduced in [12], we propose regularization techniques for shape gradients with two goals in mind. First, the required computational burden should be limited.…”
Section: Introductionmentioning
confidence: 99%
“…An complementing literature review is found in the introduction of [12]. For this work we build on results of [12], where pre-shape calculus is rigorously established.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations